Digital society, Muhammadiyah, and Islamism in the post 2024 Indonesian General Election - Muhsin Hariyanto,; Zuly Qodir, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article aims to analyses the use of electronic means such as the internet, Twitter, Facebook and Instagram with Islamic themes as a form of Islamism used in the 2014, 2019 and 2024 political campaigns to win the presidential and vice-presidential election battle in Indonesia. This article discusses the literature that shows how the networks and participation of Muslim citizens involved in the presidential election as a form of citizen participation (civil society) so that it appears the political articulation of Muslims using Islamic themes. The analysis in this article shows that the participation of Muslim citizens indirectly shows the existence of the power of Islamism in social media discursive with other Muslim citizens, as well as non-Muslim citizens who also participated in the 2014-2019-2024 election political battle. All of that shows that netizens have an ‘emotional closeness’ to the presidential-vice presidential candidate pair by using religious sentiments and networks between netizens who participate in politics as a form of netizens' political participation in the Digital Society era. The article uses the method of searching and describing data from social media databases.